Prevalence of Knee Injury in East Java’s Puslatda Fencing Athletes - Farah Yusrania; Damayanti Tinduh; Dwikora Novembri Utomo; Lilik Herawati (Surabaya Physical Medicine and Rehabilitation Journal, 2021)
Background: Fencing is one of many sports that are held in major sports events, both nationally and internationally. Fencing also has a high risk of injury, and knee injury is the most common injury site according to the authors' observations. Even so, studies on knee injuries in fencing athletes are very scarce, especially in Indonesia.Aim: To ascertain the prevalence of knee injuries and its intrinsic risk profile in fencing athletes at East Java Puslatda (regional training center).Material and Methods: The method used in this study was descriptive observational based on athletes’ health screening data, which were obtained from Sport Clinic Dr. Soetomo Academic General Hospital and athletes’ fitness data obtained from KONI.Results: This research involved 14 fencing athletes that were active in the East Java regional training center. Out of the 14 athletes who were included in this study, it was found that 1 athlete (7.1%) had a knee injury and 13 athletes (92.9%) had no knee injury. The athlete who had injured was a senior overweight female, had history of knee injury, average VO2max, normal knee ROM and alignment, and did 1-2 times leg strengthening exercises every week.Conclusion: The prevalence of knee injuries in fencing athletes at East Java regional training center is 1 in 14 athletes.